2019
DOI: 10.18203/2349-2902.isj20191029
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic laparoscopy in acute abdominal pain

Abstract: Background: Acute Abdominal pain is an important surgical problem in all age groups. Early diagnosis is needed to rule out life threatening conditions. Diagnostic laparoscopy is a modern useful tool in giving proper treatment for all needed individuals. The aim of the present endeavor is to study the use of laparoscope in patients with acute pain over the abdomen, to diagnose and confirm conditions like acute appendicitis, appendicular abscess, doudenal perforation, ileal perforation. Ovarian torsion. mass for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
0
8
0
2
Order By: Relevance
“…Laproscopy conversion rate was 0.6% and 0.6% in patients with AAP and CAP in this study and 0 (0%) in study by Rathod et al (shown in Table 6). 19 This study shows more patients with chronic pain abdomen underwent laparoscopy compared with AAP, which was not statistically significant. Though the mean duration of post-operative complications and postoperative symptomatic relief was more in patients with CAP compared with AAP, it was not statistically significant.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Laproscopy conversion rate was 0.6% and 0.6% in patients with AAP and CAP in this study and 0 (0%) in study by Rathod et al (shown in Table 6). 19 This study shows more patients with chronic pain abdomen underwent laparoscopy compared with AAP, which was not statistically significant. Though the mean duration of post-operative complications and postoperative symptomatic relief was more in patients with CAP compared with AAP, it was not statistically significant.…”
Section: Discussionmentioning
confidence: 57%
“…Rao et al study 18. Also appendicitis was 32% which was very high in study by Thawait et al and Subramaniam et al 79% diverticulitis was 0.6% in current study which was very low, compared with study by Bahram et al it was 5% (shown in Table6) 16,17,19. Causes of chronic abdomen in current study was chronic appendicitis (23/13.7%) which was low compared with study by Brahman et al (23.75%) and Schrenk et al (32.25%) 17,20.…”
mentioning
confidence: 47%
“…Subramaniam [1] reported acute appendicitis as the most common cause of acute abdomen [79.0%; high percentage than the current work], followed by perforated peritonitis [9.0% [7% duodenal & 2% ileal]].…”
Section: Discussionmentioning
confidence: 64%
“…So diagnostic accuracy of radiological investigations was 60.0% [18 out of 30 cases] while the same for laparoscopy was 90.0% [27 out of 30 cases]. Subramaniam [1] reported that, laparoscopy was able to diagnose 7.0% over the radiological work up in acute abdomen [e.g., mesenteric ischemia, ectopic pregnancy, twisted ovarian cyst and ileal perforation].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation